A necessary and sufficient condition for the nontrivial limit of the derivative martingale in a branching random walk. (September 2015) - Chen, Xinxin
Abstract : We consider a branching random walk. Biggins and Kyprianou (2004) proved that, in the boundary case, the associated derivative martingale converges almost surely to a finite nonnegative limit, whose law serves as a fixed point of a smoothing transformation (Mandelbrot's cascade). In this paper, we give a necessary and sufficient condition for the nontriviality of the limit in this boundary case.